Association of results of the glutaraldehyde coagulation test with plasma acute phase protein concentrations and hematologic findings in hospitalized cows - Trefz, Florian M.; Balmer, Martina; Peters, Laureen M.; Bruckmaier, Rupert M.; Meylan, Mireille (Frontiers in Veterinary Science, 2024)
The glutaraldehyde test (GAT) allows for animal-side semi-quantitative estimation of fibrinogen and gamma-globulin concentrations in blood samples of adult cattle and therefore detection of inflammatory disease conditions. However, the test has potential limitations, especially due to the latency period until sufficiently high fibrinogen and/or gamma-globulin concentrations are reached. The aim of the present study was therefore to assess the association between results of GAT with other inflammatory markers including hematologic variables, fibrinogen, plasma haptoglobin and serum amyloid A (SAA) concentrations. For the purpose of this prospective observational study, a convenience sample of 202 cows with a broad range of inflammatory and non-inflammatory clinical conditions was included. The GAT was run on EDTA blood, fibrinogen was measured using the Clauss and the heat precipitation method, and commercially available ELISA tests were used for determination of plasma haptoglobin and SAA concentrations. Shortened GAT coagulation times were more closely correlated to serum globulin (rs = -0.72) than to plasma fibrinogen concentrations measured with the heat precipitation (rs = -0.64) and the Clauss method (rs = -0.70). Cows with a markedly (≤ 3 minutes) or moderately (4 -6 minutes) shortened coagulation time had higher (P < 0.001) plasma haptoglobin and SAA concentrations than cows with a negative test result. Total leukocyte, monocyte and neutrophil concentrations did not differ significantly between groups. An identified cut-off for the GAT coagulation time of ≤ 14 minutes had a sensitivity and specificity of 54.4% and 100%, respectively, for the prediction of an inflammatory state based on clinical findings and/or increased plasma haptoglobin or SAA concentrations. In conclusion, this study demonstrates considerable diagnostic agreement between positive GAT results and increased plasma concentrations of haptoglobin and SAA. Despite high specificity, the test lacks sensitivity in case of acute inflammatory conditions indicating that plasma acute phase protein concentrations and hematologic findings can provide additional diagnostic information if the GAT is negative.